MAGAZ3NE: Evidence for Galactic Conformity in z ≳ 3 Protoclusters - Ian McConachie; Gillian Wilson; Ben Forrest; Z. Cemile Marsan; Adam Muzzin; M. C. Cooper; Marianna Annunziatella; Danilo Marchesini; Percy Gomez; Wenjun Chang; Stephanie M. Urbano Stawinski; Michael McDonald; et al. (The Astrophysical Journal)
We examine the quiescent fractions of massive galaxies in six z ≳ 3 spectroscopically confirmed protoclusters in the COSMOS field, one of which is newly confirmed and presented here. We report the spectroscopic confirmation of MAGAZ3NE J100143+023021 at $z={3.122}_{-0.004}^{+0.007}$ by the Massive Ancient Galaxies At z > 3 NEar-infrared (MAGAZ3NE) survey. MAGAZ3NE J100143+023021 contains a total of 79 protocluster members (28 spectroscopic and 51 photometric). Three spectroscopically confirmed members are star-forming ultramassive galaxies (UMGs; $log(M_{\star }/M_{\odot })$ > 11), the most massive of which has $log(M_{\star }/M_{\odot })$ $\,=\,{11.15}_{-0.06}^{+0.05}$ . Combining Keck/MOSFIRE spectroscopy and the COSMOS2020 photometric catalog, we use a weighted Gaussian kernel density estimator to map the protocluster and measure its total mass ${2.25}_{-0.65}^{+1.55}× {10}^{14}\,M_{\odot }$ in the dense “core” region. For each of the six COSMOS protoclusters, we compare the quiescent fraction to the status of the central UMG as star-forming or quiescent. We observe that galaxies in these protoclusters appear to obey galactic conformity: Elevated quiescent fractions are found in protoclusters with UVJ -quiescent UMGs and low quiescent fractions are found in protoclusters containing UVJ star-frming UMGs. This correlation of star formation/quiescence in UMGs and the massive galaxies nearby in these protoclusters is the first evidence for the existence of galactic conformity at z > 3. Despite disagreements over mechanisms behind conformity at low redshifts, its presence at these early cosmic times would provide strong constraints on the physics proposed to drive galactic conformity.